Age of eradication and failure rates of clarithromycin‐containing triple therapy for Helicobacter pylori: A 15‐year population‐based study. Issue 3 (12th April 2022) - Jiang, Fang; Guo, Chuan‐Guo; Cheung, Ka Shing; Li, Bofei; Law, Simon Y. K.; Leung, Wai K.
Abstract: Background: Failure rates of clarithromycin‐containing triple therapy for H. pylori are rising. To determine the trend of failure rates of clarithromycin‐containing triple therapy in different age groups in Hong Kong over the past 15 years. Materials and Methods: This is a population‐based retrospective age‐period‐cohort study involving all adult H. pylori ‐infected patients who had received the first course of clarithromycin‐containing triple therapy in 2003–2017. Failed eradication was identified by the need of retreatment within 2 years of eradication. Logistic regression model was used to characterize the risk of retreatment. Results: 113, 526 H. pylori ‐infected patients were included. The overall failure rate increased from 4.83% in 2003 to 10.2% in 2016 ( p for linear trend <0.001). When stratified by age of eradication, patients 75 years or above had the lowest retreatment rate of 5.11%, which progressively increased in younger patients (60–74 years: OR 1.26, 95% CI 1.15–1.38; 45–59 years: OR 1.36, 95% CI 1.24–1.48; 18–44 years: OR 1.55, 95% CI 1.41–1.69). The results remained consistent when stratified by year of birth, and period of eradication. Other risk factors for retreatment included female (OR 1.24, 95% CI 1.18–1.30), triple therapy containing metronidazole (OR 2.30, 95% CI 2.12–2.50), and shorter duration of therapy (10 days: OR 0.88, 95% CI 0.79–0.97; 14 days: OR 0.67, 95% CI 0.58–0.77 vs 7 days). Conclusions: While failure rates of clarithromycin‐containing triple therapy progressively increased over the past 15 years, the failure rate was particularly high among younger patients, which could undermine the potential benefits of early H. pylori eradication.